USING FORMULATOR TARSIA TO CREATE COLLABORATIVE ACTIVITIES IN MATHEMATICS CLASSROOM - Qomaria, Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The purpose of this study was to establish if students could engage on collaborative activities which were supported by Formulator Tarsia. This study was specially concerned with the engagement of 8 th grade students in learning mathematics. Data were collected through direct observations, open questionnaires, and dialogue with some students. The result showed that students engaged with puzzle and domino activities really well and there was some good dialogue between them about checking the answers and the puzzle piece positions. Students said that they had really enjoyed the activities and they worked very well together in small group. Solving mathematics puzzle and domino created by Formulator Tarsia were fun activities that can generate dialogue, reactivate prior knowledge, and can encourage higher order thinking.